Aftereffects of Saccades Explored in a Dynamic Neural Field Model of the Superior Colliculus - Zhiguo Wang; Jason Satel; Thomas P. Trappenberg; Raymond M. Klein (Journal of Eye Movement Research)
When viewing a scene or searching for a target, an observer usually makes a series of saccades that quickly shift the orientation of the eyes. The present study explored how one saccade affects subsequent saccades within a dynamic neural field model of the superior colliculus (SC). The SC contains an oculocentric motor map that encodes the vector of saccades and remaps to the new fixation location after each saccade. Our simulations demonstrated that the observation that saccades which reverse their vectors are slower to initiate than those which repeat vectors can be explained by the afore-mentioned remapping process and the internal dynamics of the SC. How this finding connects to the study of inhibition of return is discussed and suggestions for future studies are presented.